The Effect of Neonicotinoids Exposure on Oreochromis niloticus Histopathological Alterations and Genotoxicity - Islam M. El-Garawani; Elsayed A. Khallaf; Alaa A. Alne-na-ei; Rehab G. Elgendy; Hassan M. Sobhy; Adel Khairallah; Heba M. R. Hathout; Farag Malhat; Amany E. Nofal (Bulletin of Environmental Contamination and Toxicology, 2022)
This study aimed to examine the side effects of selected neonicotinoids (Acetamiprid, Aceta, and Imidacloprid, Imid) on Oreochromis niloticus juveniles. The acute toxicity, Probit method, revealed an LC 50 of 195.81 and 150.76 ppm for Aceta/96 h and Imid/72 h respectively. The fish were divided into three groups that were exposed, for 21 days (n = 5/replicate), to 1/10 of the LC 50 of either neonicotinoids, however, the third was an unexposed control group. Results of erythrocytic micronucleus (MN), and nuclear abnormalities (NA) showed that Aceta and Imid exposure caused a significant ( p < 0.05) increase in MN by ~ 2.2 and ~ 10 folds, respectively relative to control. NAs occurred at the order of kidney-shaped > budding > binucleated in Aceta, however, budding > binucleated > kidney-shaped was noticed in the Imid group. Histopathological changes in gills, liver, and muscles were observed significantly in both exposed groups with more severity in the Imid group. Collectively, Aceta and Imid have potential genotoxicity and histopathological alterations in O. niloticus .